Differences of the microstructural evolution of Cu powder during continuous and interrupted mechanical milling. (27th May 2017) - Cipolloni, Giulia; Menapace, Cinzia; Pellizzari, Massimo; Ischia, Gloria
ABSTRACT: Water atomised copper powders (AT-Cu) have been processed by continuous and interrupted mechanical milling (MM) for different milling times. For continuous cycle the powders are subjected first to a severe flattening process and then to an intense welding phenomenon. In the case of interrupted cycle MM behaviour proceeds with an intense fracturing process. By quantitative X-ray-diffraction analysis the interrupted cycle shows constantly a delay of the microstructure evolution with all the phenomena shifted at longer milling time. For both types of cycle crystalline size decreases down to 20 nm. After 6000 min of interrupted MM the formation of Cu2 O has been revealed and a strong dependency between oxygen content and microstructural parameter has been attested analysing the variations of lattice parameter and lattice strain. When the interstitial oxygen atoms lose their Cottrell locking action dislocation annihilation occurs leading to a reduction of dislocation density and lattice strain.